2023
DOI: 10.1021/acs.nanolett.3c00221
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Lactate-Associated Immunosuppression against Intracellular Bacteria Using Thermoresponsive Nanoparticles for Septic Arthritis Therapy

Abstract: Intracellular bacteria are the major contributor to the intractability of septic arthritis, which are sequestered in macrophages to undermine the innate immune response and avoid the antibacterial effect of antibiotics due to the obstruction of the cell membrane. Herein, we report a thermoresponsive nanoparticle, which consists of a phase-change material shell (fatty acids) and an oxygen-producing core (CaO 2 −vancomycin). Under external thermal stimulation, the shell of the nanoparticle transforms from a soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…It was reported that macrophages can activate innate immune function to defend intracellular bacteria mainly by oxidative stress. Therefore, we analyzed whether PECs can improve antibacterial activity by enhancing the oxidative stress of infected macrophages. We first detected intracellular ROS levels by 2′,7′-dichlorofluorescein diacetate (DCFH-DA) probe.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that macrophages can activate innate immune function to defend intracellular bacteria mainly by oxidative stress. Therefore, we analyzed whether PECs can improve antibacterial activity by enhancing the oxidative stress of infected macrophages. We first detected intracellular ROS levels by 2′,7′-dichlorofluorescein diacetate (DCFH-DA) probe.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages can eradicate colonized bacteria directly and indirectly by releasing lysozyme, producing enormous ROS, and so on, thereby reducing extracellular PAMPs accumulation in infected areas. Recent research has also focused on utilizing biomaterials to generate ROS for bactericidal performance. However, chronically excessive ROS produced by these materials tend to disrupt mitochondrial homeostasis and impair macrophage polarization over time . Therefore, it is challenging for biomaterials to skillfully integrate extracellular PAMPs clearance with intracellular mitochondrial regulation based on ROS variation.…”
mentioning
confidence: 99%